Detection of unmarked graves using Ground Penetrating Radar - Mohammed, Anas A.; Mahdi , Alaa S. (Iraqi Journal of Science, 2022)
Ground penetrating radar (GPR) is one of the Remote Sensing methods that utilize electromagnetic waves in the detection of subjects below the surface to record Once the data were collected, it could be presented in map and 2D and 3D. GPR method was applied in detecting graves (Tel Alags archaeological) fact, within the administrative border to spend Rumitha can be challenging. Due to the sensitivity of these sites, the challenge is to explore the subsurface without disturbing the soil Some cemeteries are hundreds of years old. Often records are vague or incomplete and there may be serious doubt about the precise extent of a cemetery .GPR is the most practical way to sort out the site was to carry out a detailed grid survey. A Noggin 250 MHz Smart Cart configuration was employed. Survey grid was 20 x 5 m with line spacing of 0.5 m. Data were acquire in 1 hour and first order maps were created on site..